IN VITRO ANTIBACTERIAL ACTIVITY AND THE EFFECT OF EXPLANT TYPE AND EXTRACTION SOLUTION ON SOME BIOCHEMICAL PROPERTIES OF RUMEX TUBEROSUS: Life Sciences-Microbiology - YOUSEF GHASEMI; MOHAMMAD ALI EBRAHIMZADEH; SAREH REZAEI; MAHDIEH TAHERI; SEYYEDEH FATEMEH HASHEMIAN; ABBAS ALI DEHPOUR (International Journal of Life Science and Pharma Research, 2022)
Medicinal plants contain wide range of secondary metabolites which have being used in many aspects of pharmaceutical science. This paper was conducted to determine the effect of extraction solution and plant part on the antioxidant activities, flavonoid and phenol contents and assay of antimicrobial activity of Rumex tuberosus. High antioxidant activity with 0.65 mg/ml was observed in flower when it extract by methanol solvent. Also methanol increase the total phenol content in all parts of the plant in comparison with chloroform but flavonoid result is completely different and the highest flavonoid was obtained by chloroform extraction. Antimicrobial test approved that Gram-positive bacteria have been more impressed than gram-negative bacteria by methanol extraction of R. tuberosus. Two strains (P. mirabilis, K. pneumonia) could not control by R. tuberosus ethanol extract.